Theory of Electroelasticity - Kuang, Zhen-Bang.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
Theory of Electroelasticity analyzes the stress, strain, electric field and electric displacement in electroelastic structures such as sensors, actuators and other smart materials and structures. This book also describes new theories such as the physical variational principle and the inertial entropy theory. It differs from the traditional method by using the physical variational principle to derive the governing equations of the piezoelectric material, whereas the Maxwell stress is obtained automatically. By using the inertial entropy theory, the temperature wave equation is obtained very easily. The book is intended for scientists, researchers and engineers in the areas of mechanics, physics, smart material and control engineering as well as mechanical, aeronautical and civil engineering, etc. Zhen-Bang Kuang is a professor at Shanghai Jiao Tong University.
Introduction Continuum Thermodynamics -- Physical variational Principle and Governing Equations -- Generalized two dimensional electroelastic problem -- Linear inclusion and related problems -- Some problems in more complex materials with deffects -- Electroelastic wave -- Three dimensional and applied electroelastic problem -- Failure theory in piezoelectric materials.
Keywords: Engineering; Mechanics; Materials; Civil engineering; Engineering; Continuum Mechanics and Mechanics of Materials; Structural Materials; Mechanics; Control; Materials Science, general; Civil Engineering